THESE QUALITIES OF THE POET WERE MANIFESTED - Boyxurozov Diyorbek Sherzod ugli (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Annotation. The entire work of Maqsud Shaykhzoda is full of a deep political publicistic spirit. His poetic, dramatic works are in harmony with the times, no matter what theme they are devoted to. Therefore, the direct service of a creator of this type in the genre of journalism. Well, you know, increased means light, light, clarity. Indeed, our intelligentsia was called upon to do the best of knowledge, enlightenment, culture, education..."With this word, it was as if those who were sitting in the Enchanted Assembly Hall had a thunderous applause.